Peran Lembaga Pengembangan Tilawah Al-Qur’an (LPTQ) Provinsi Sumatera Utara Dalam Cabang Tilawah - Fitri Agustina Sari; Sellindra Rizqi Utami; Nafiza Fadia Anwar; Putri Ayunda Br Limbong; Ade Rahmat Rezky Tumanggor (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
The fact states that Musabaqah Recitations of the Qur'an (MTQ) are considered as a worship activity for Muslims. That is the implementation of the existence of MTQ when described universally. The purpose of this research is to find out the role of LPTQ North Sumatra in improving the performance of Qari and Qari'ah. To find out what challenges are faced by LPTQ in improving the performance of Qari and Qari'ah. The quantitative research method can also be interpreted as a research method based on the philosophy of positivism, used for research on certain populations and samples, data collection using research instruments, data analysis is quantitative/statistical in nature, with the aim of testing established hypotheses. Until now it has been running as the North Sumatra LPTQ program itself. However, both in the implementation and the coaching process there are still many shortcomings and this is still being questioned why until now the North Sumatra Caravan has not been able to make good achievements at the national level, especially the Tilawatil Qur'an branch, namely for Qari' and Qari'ah in particular. North Sumatra Province is one of the provinces that is considered to have good strength according to other provinces. Many Qori' and Qori'ah have extraordinary abilities and talents so that they are able to compete with other participants in the National MTQ event. Keywords: LPTQ, recitations